REKAYASA ULANG PERANGKAT LUNAK MENGGUNAKAN ITERATIF PADA WEBSITE SMART VILLAGE KABUPATEN SAMPANG: SOFTWARE REENGINEERING USING ITERATIVES ON THE SMART VILLAGE WEBSITE OF SAMPANG DISTRICT - Almas'Udi; Wildan Suharso (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Digital transformation through Smart Villages aims to improve the effectiveness of village governance. However, the implementation of the Smart Village Website in Sampang Regency previously faced technical constraints, such as an unresponsive user interface, suboptimal database structure, slow processing, and sub-optimal features. This study aims to improve service quality and system efficiency through software reengineering using an iterative approach. The stages include legacy system analysis, data classification, database and function redesign, component adaptation, data migration, equivalence testing (Black-Box Testing), and residual data clearance. The results show that reengineering successfully restructured the database by removing irrelevant attributes and residual data. Redesigning functions in main components resulted in a more interactive interface. Performance testing indicates a significant increase in page loading speed, averaging 71% to 73% across all main modules. In conclusion, the iterative reengineering method is effective in producing a more stable, efficient, and significantly better-performing system than the legacy system.